Structural features of the invariant chain fragment CLIP controlling rapid release from HLA-DR molecules and inhibition of peptide binding. - Kropshofer, Harald; Vogt, Anne B.; Hämmerling, Günter J. (Proceedings of the National Academy of Sciences of the United States of America, 1995)
The invariant chain (Ii) prevents binding of ligands to major histocompatibility complex (MHC) class II molecules in the endoplasmic reticulum and during intracellular transport. Stepwise removal of the Ii in a trans-Golgi compartment renders MHC class II molecules accessible for peptide loading, with CLIP (class II-associated Ii peptides) as the final fragment to be released. Here we show that CLIP can be subdivided into distinct functional regions. The C-terminal segment (residues 92-105) of the CLIP-(81-105) fragment mediates inhibition of self- and antigenic peptide binding to HLA-DR2 molecules. In contrast, the N-terminal segment CLIP-(81-98) binds to the Staphylococcus aureus enterotoxin B contact site outside the peptide-binding groove on the alpha 1 domain and does not interfere with peptide binding. Its functional significance appears to lie in the contribution to CLIP removal: the dissociation of CLIP-(81-105) is characterized by a fast off-rate, which is accelerated at endosomal pH, whereas in the absence of the N-terminal CLIP-(81-91), the off-rate of C-terminal CLIP-(92-105) is slow and remains unaltered at low pH. Mechanistically, the N-terminal segment of CLIP seems to prevent tight interactions of CLIP side chains with specificity pockets in the peptide-binding groove that normally occurs during maturation of long-lived class II-peptide complexes.